Terapia afecţiunilor osteoarticulare degenerative la câine - Bulai, Anca; Crivineanu, Maria (Medicamentul Veterinar, 2017)
The degenerative joint disease, newly called osteoarthritis, is a common affection found in human and animal sectors. It is generally mentioned as a noninflammatory disease of articular cartilage the causes being represented by natural aging, traumas and other affections. The treatments used in the veterinary medicine aim in treating the inflammatory part of this disease, nonsteroidian inflammatories being used firstly to stop the evolution of the disease and to stop the clinical sings manifested by the affected animals, mainly due to the local pain. However, there are various groups of analyzed drugs that can be used with this purpose.